Results of therapy of chronic urticaria in patients with IgE-dependent and IgE-independent disease profile - N. N. Zhukova; K. S. Mazokha; M. V. Manzhos; E. V. Aseeva (Медицинская иммунология, 2023)
The main mechanism for the occurrence of urticaria is the degranulation of mast cells. It has been proven that, regardless of the activation pathway, clinical manifestations will not differ. According to the literature, up to half of cases of chronic spontaneous urticaria are autoimmune in nature, can be combined with autoimmune thyroid disease, SLE, etc., and have a more severe course.In therapy, antihistamines are traditionally used. However, some patients do not respond to the treatment, even with a multiple increase in doses. In the treatment of urticaria resistant to traditional antihistamines, the use of Omalizumab is recommended. The purpose of the study: to determine the profile of patients with chronic urticaria, as well as to evaluate the effectiveness of treatment with Omalizumab in patients with IgE- dependent and IgE-independent chronic urticaria.Eight-one patients with chronic urticaria (60 adults, 21 children) were examined. Patients before the start of therapy had a long history of CU: from 1 to 20 years. Patients before the start of therapy were treated with antihistamines, but no control was obtained. An increase in the level of serum IgE was detected in 51.7% of cases in adults and 42% in children. Concomitant sensitization was determined in 48.3% of adults and 76.2% of children. In children, food, epidermal and pollen sensitization was the most common. Pollen and epidermal sensitization were more common in adults. The level of eosinophilia in the group with IgE-dependent was more pronounced than in other group (p = 0.0097). After 6 months, the group with IgE-dependent showed an improvement in the symptom score (UCT) from 3.1 CI (1.5-4.6) to 12.2 CI (10.8-13.7), (p = 0.0001). In other group, symptoms improved from 0.63 CI (0.36-1.6) to 8.1 CI (5-11.2) after 6 months (no control). After 6 months of genetically engineered biological therapy (GIBT), complete control over the symptoms of CU in group 1 was obtained in 66.7% of patients, partial — in 33.7%. In the second group, in 33.3% of cases, positive treatment results could not be achieved. Thus, genetically engineered biological therapy with Omalizumab increases the control over the course of CU. Treatment outcomes are higher in patients with an IgE-dependent disease profile.